Platelet-Rich Plasma Powder: A New Preparation Method for the Standardization of Growth Factor Concentrations. (March 2017) - Kieb, Matthias; Sander, Frank; Prinz, Cornelia; Adam, Stefanie; Mau-Möller, Anett; Bader, Rainer; Peters, Kirsten; Tischer, Thomas
Background: Platelet-rich plasma (PRP) is widely used in sports medicine. Available PRP preparations differ in white blood cell, platelet, and growth factor concentrations, making standardized research and clinical application challenging. Purpose: To characterize a newly standardized procedure for pooled PRP that provides defined growth factor concentrations. Study Design: Controlled laboratory study. Methods: A standardized growth factor preparation (lyophilized PRP powder) was prepared using 12 pooled platelet concentrates (PCs) derived from different donors via apheresis. Blood samples and commercially available PRP (SmartPrep-2) served as controls (n = 5). Baseline blood counts were analyzed. Additionally, single PCs (n = 5) were produced by standard platelet apheresis. The concentrations of vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), platelet-derived growth factor AB (PDGF-AB), transforming growth factor β1 (TGF-β1), insulin-like growth factor 1 (IGF-1), interleukin (IL)–1α, IL-1β, and IL-1 receptor agonist (IL-1RA) were analyzed by enzyme-linked immunosorbent assay, and statistical analyses were performed using descriptive statistics, mean differences, 95% CIs, and P values (analysis of variance). Results: All growth factor preparation methods showed elevated concentrations of the growth factors VEGF, bFGF, PDGF-AB, and TGF-β1 compared with those of whole blood. Large interindividual differences were found in VEGF and bFGF concentrations. Respective values (mean ± SD in pg/mL) for whole blood, SmartPrep-2, PC, and PRP powder were as follows: VEGF (574 ± 147, 528 ± 233, 1087 ± 535, and 1722), bFGF (198 ± 164, 410 ± 259, 151 ± 99, and 542), PDGF-AB (2394 ± 451, 17, 846 ± 3087, 18, 461 ± 4455, and 23, 023), and TGF-β1 (14, 356 ± 4527, 77, 533 ± 13, 918, 68, 582 ± 7388, and 87, 495). IGF-1 was found in SmartPrep-2 (1539 ± 348 pg/mL). For PC (2266 ± 485 pg/mL), IGF-1 was measured at the same levels of whole blood (2317 ± 711 pg/mL) but was not detectable in PRP powder. IL-1α was detectable in whole blood (111 ± 35 pg/mL) and SmartPrep-2 (119 ± 44 pg/mL). Conclusion: Problems with PRP such as absent standardization, lack of consistency among studies, and black box dosage could be solved by using characterized PRP powder made by pooling and lyophilizing multiple PCs. The new PRP powder opens up new possibilities for PRP research as well as for the treatment of patients. Clinical Relevance: The preparation of pooled PRP by means of lyophilization may allow physicians to apply a defined amount of growth factors by using a defined amount of PRP powder. Moreover, PRP powder as a dry substance with no need for centrifugation could become ubiquitously available, thus saving time and staff resources in clinical practice. However, before transferring the results of this basic science study to clinical application, regulatory issues have to be cleared.